Human Nature: An Islamic Perspective - Abdul Razak, Mohd Abbas (Journal of Islam in Asia (E-ISSN 2289-8077), 2012)
Human nature is a widely and popularly discussed topic not only in the East but also in the West. This topic has drawn people from diverse backgrounds of knowledge to explore and investigate who or what man is in relation to his Creator and other creations that exist in the universe. The research on man and the attempts to answer many of the intricate questions related to his creation and existence which started in the ancient past is still on-going. The fact that the latest findings on man have added information to the existing body of knowledge makes the study on human nature a dynamic and perennial one. Within the scope of this paper, the researcher has made an attempt to discuss the topic on human nature from the Islamic perspective. In discussing the nature of man, the researcher has ventured into the physical and metaphysical realms of his existence as described in the Qur’an. Besides that, the researcher has also entertained some discussions on how man has been perceived in the mainstream Western and Islamic psychologies. In concluding the paper, the researcher has anchored the discussion as to why the study on human nature is important.